Differentiating between tackiness and stickiness and their induction in foods. (June 2019) - Noren, Nancy Ellen; Scanlon, Martin G.; Arntfield, Susan D.
Abstract: Stickiness is an important property in foods having both positive and negative aspects for processors and consumers. It is typically considered a negative characteristic by processors as it leads to problems such as clogging, scaling and fouling of equipment. These issues may be better addressed by defining the conditions required for sticky or tacky behaviour. In recent years, the term "tackiness" has become synonymous with stickiness although they describe different phenomena. In this paper, the difference between tackiness and stickiness and, the related terms, adhesion and cohesion will be outlined, focusing on the food and interfacial properties responsible for these behaviours. Highlights: Rheological terminology used in research on adherence to processing equipment surfaces clarified. Definitions of tackiness, stickiness, cohesion and adhesion made based on commonalities within multiple research studies. Food and interfacial properties responsible for stickiness and tackiness in foods summarized. Stickiness induction linked to food material properties and interfacial properties of food and process equipment surfaces.